Pengaruh Arus Listrik dan Filler dengan Kampuh X Terhadap Sifat Mekanik Sambungan Las SMAW pada Baja St 37 - Bambang Teguh Baroto; Petrus Heru Sudargo (Politeknosains, 2017)
Applications welded joints are still the main choice in the field of construction. This is because the construction becomes lighter, cheaper and faster in the welding process. Weld strength is strongly influenced by the composition and properties of the based metal and filler, and welding process. The purpose of this study was to investigate the hardness and SMAW( Metal Shielded Arc Welding) welding joint microstructure of low carbon steel due to variations in electrical current input. Research using ST 37 steel material and variation filler LB-5U and NC-36L, with a variation of the electric current of 80 A, 100 A and 120 A. Result of extension of characteristic with interesting examination, hardness, and micro structure. Interesting examination use standard of JIS Z2201. Result of research indicate that extension of las with NC-36L filler and use current equal to 120 A have highest interesting strength that is 38,36 kN/m2, while extension of las with LB-5U filler and use current equal to 80 A have interesting strength lowered that is 15,80 kN/m2. Hardness test using rockwell hardness testing machine, while the micro-structure photograph using an optical microscope. The hardness results of welds decreases, while the predominantly cementite microstructure with finer sizes.